Penggunaan Media Pembelajaran Multimedia Interaktif Terhadap Hasil Belajar Seni Budaya (Tari) Di Kelas XI SMA Negeri 15 Padang - Dinda Syahiba; Yuliasma Yuliasma (Student Scientific Creativity Journal, 2023)
This study aims to describe the influence of Interactive Multimedia learning media on class XI Cultural Arts (Dance) subjects at SMA N 15 Padang. This type of research is experimental research. The population in this study amounted to 250 students divided into 10 classes with a sample of 54 students divided into 2 classes. The instrument used is an objective test. Data is collected through observation, tests and documentation. The data processing steps are scoring, data processing and t-test. The results showed that the use of Interactive Multimedia learning media had a good influence on student learning outcomes compared to the use of conventional learning media in the form of printed books and blackboards. Judging from the results of the analysis of students' pretest and posttest scores in the experimental class and control class, the analysis was carried out with a statistical test in the form of an independent sample t test as a hypothesis test. The highest score in the experimental class was 100 and in the control class 87.5, while the lowest score in the experimental class was 58.3 and the control class was 25. So it is known that there is a significant difference between the scores of experimental class students and the control class. In this case, the scores of experimental class students who use Interactive Multimedia learning media are higher than the scores of control class students who use conventional learning media in the form of printed books and whiteboards